Predicting hypertension using waist circumference in obese Indonesian adolescents - Elvietha Alamanda; Endy Paryanto Prawirohartono; Nenny Sri Mulyani (Indonesian Pediatric Society, 2010)
Background Increasing prevalence of pediatric obesity and hypertension demonstrate the urgent need for early intervention. Waist circumference (WC) provides a measurement of central obesity, which has been specifically associated with cardiovascular risk factor including hypertension.Objectives To identify the optimal cutô€€¹off point of we in predicting hypertension in obese adolescents.Methods We randomly recruited 115 adolescents aged 12-17 years from schools in Yogyakarta, Central Java, Indonesia. We measured height, weight, WC, and blood pressure in 109 subjects. Optimum WC cut-offs to predict hypertension were determined using receiver-operating characteristic (ROC).Results The optimum WC cut off point to predict any hypertension in adolescents was at the 88.95 cm with 97.8% sensitivity and 47.3% specificity. Ageô€€¹specific cutô€€¹off points for subjects < 15 year old was 90.1 cm with 91.7% sensitivity and 58%specificity, and for subjects 2: 15 year old was 103.5 cm with 75% sensitivity and 88% specificity.Conclusions Waist circumference can be used to predict hypertension in obese adolescents with fair sensitivity and specificity. Waist circumference values associated with hypertension in adolescents vary with age and ethnicity.